Things You Can Do When You’re Dead by Tricia J. Robertson - Soto-Espinosa, Jesus (Journal of Scientific Exploration, 2014)
This book presents an opportunity for those persons who have not studied the research literature on apparitions, mediumship, life after death, poltergeist activity, paranormal healing and reincarnation. The reader will encounter the richness of case studies with systematic scientific questioning. The author examines how these experiences influence the lives of those who report these phenomena. What follows is a brief summary of a typical of case study that Robertson presents: A shopkeeper experienced an apparition of a man, who he immediately identified as one of his customers whom had deceased over 6 years ago, on the ceiling of his shop while painting. The apparition pointed and told him, "Tell them not to do it, everything will be all right". The shopkeeper remained with shock and disbelief. However, the following day the widow of the apparition attended his shop as usual. He then told her about his experience. When he finished the lady's reaction was totally un expected since she threw her arms around him and thanked him while saying that she had already been given similar information by someone else, and this confirmed it. The shopkeeper had no clue as to what it was all about. Two weeks latter this lady explained that her son had been wrongly accused of a crime, but the evidence was such that, if found guilty, he could have been given a jail sentence in an adult jail. The family did not want this to happen and had thought of taking him to Southern Ireland to hide, which would mean that he would not appear at court and equally that he would not be able to return to Scotland again. However, the woman took the "advice" from her husband (via the shopkeeper) and when the boy did appear in court the case was dismissed. The judge simply said "No case to answer". The shopkeeper had never experienced anything like this before or after this event. (p. 11-13) From here on the author offers her analysis of the case.